2000
DOI: 10.1007/s002840010105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogel/Silver Coatings on In Vitro Adhesion to Catheters of Bacteria Associated with Urinary Tract Infections

Abstract: Sections of sterile all-silicone-, hydrogel/silver-all-silicone-, and hydrogel/silver-latex-Foley urinary catheters were exposed to suspensions of bacteria and Candida albicans associated with urinary tract infections. The adhesion of these microorganisms to the catheters was determined with a radiolabel-cell procedure and scanning electron microscopy. Anomalous data with the radiolabel procedure were produced with the hydrogel/silver-latex catheters for certain species. These aberrant data were related to adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(75 citation statements)
references
References 6 publications
2
69
2
2
Order By: Relevance
“…The insensitivity of biofilm bacteria to antibiotics is a function of cell wall composition, surface structure, and phenotypic variation in enzymatic activity (8,14). It has also been suggested that the negatively charged exopolysaccharide is very effective in protecting bacterial cells from cationic antibiotics by restricting their permeation (2).In the last decade, several strategies to control biofilm growth on medical devices have been suggested, including using topical antimicrobial ointments, minimizing the length of time of catheterization, using catheters provided with a surgically implanted cuff (12), and coating the catheter lumen with antimicrobial agents (1,7,9,19,26,27). Enzymes involved in bacterial cell wall synthesis could provide novel targets for the development of antibiofilm agents.…”
mentioning
confidence: 99%
“…The insensitivity of biofilm bacteria to antibiotics is a function of cell wall composition, surface structure, and phenotypic variation in enzymatic activity (8,14). It has also been suggested that the negatively charged exopolysaccharide is very effective in protecting bacterial cells from cationic antibiotics by restricting their permeation (2).In the last decade, several strategies to control biofilm growth on medical devices have been suggested, including using topical antimicrobial ointments, minimizing the length of time of catheterization, using catheters provided with a surgically implanted cuff (12), and coating the catheter lumen with antimicrobial agents (1,7,9,19,26,27). Enzymes involved in bacterial cell wall synthesis could provide novel targets for the development of antibiofilm agents.…”
mentioning
confidence: 99%
“…The mechanism of antibacterial activity proposed is associated with an initial inhibition of primary adherence due to the hydrogel hydrophilicity, followed by secondary biocidal activity of the silver coating [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…Bu enfeksiyonların önüne geçmek amacıyla son yıllarda bazı antimikrobiyal ajanlar ve biyofilm oluşumunu inhibe edici maddelerle kaplanmış kateterler kullanıma girmiştir (23)(24)(25) . Gümüş kaplı kateter kullanıldığında üriner infeksiyon gelişme oranı %30'luk bir azalma göstermiştir (26) .…”
Section: Discussionunclassified